Revisiting chromatin binding of the Arabidopsis UV-B photoreceptor UVR8. Issue 1 (December 2016) - Binkert, Melanie; Crocco, Carlos; Ekundayo, Babatunde; Lau, Kelvin; Raffelberg, Sarah; Tilbrook, Kimberley; Yin, Ruohe; Chappuis, Richard; Schalch, Thomas; Ulm, Roman
Abstract Background Plants perceive UV-B through the UV RESISTANCE LOCUS 8 (UVR8) photoreceptor and UVR8 activation leads to changes in gene expression such as those associated with UV-B acclimation and stress tolerance. Albeit functionally unrelated, UVR8 shows some homology with RCC1 (Regulator of Chromatin Condensation 1) proteins from non-plant organisms at the sequence level. These proteins act as guanine nucleotide exchange factors for Ran GTPases and bind chromatin via histones. Subsequent to the revelation of this sequence homology, evidence was presented showing that UVR8 activity involves interaction with chromatin at the loci of some target genes through histone binding. This suggested a UVR8 mode-of-action intimately and directly linked with gene transcription. However, several aspects of UVR8 chromatin association remained undefined, namely the impact of UV-B on the process and how UVR8 chromatin association related to the transcription factor ELONGATED HYPOCOTYL 5 (HY5), which is important for UV-B signalling and has overlapping chromatin targets. Therefore, we have investigated UVR8 chromatin association in further detail. Results Unlike the claims of previous studies, our chromatin immunoprecipitation (ChIP) experiments do not confirm UVR8 chromatin association. In contrast to human RCC1, recombinant UVR8 also does not bind nucleosomes in vitro. Moreover, fusion of a VP16 activation domain to UVR8 did not alter expression of proposed UVR8 target genes in transient gene expression assays. Finally, comparison of the Drosophila DmRCC1 and the Arabidopsis UVR8 crystal structures revealed that critical histone- and DNA-interaction residues apparent in DmRCC1 are not conserved in UVR8. Conclusion This has led us to conclude that the cellular activity of UVR8 likely does not involve its specific binding to chromatin at target genes.